Sm-Nd mineral isochron age of sapphirine-quartz gneiss from the Mt. Riiser-Larsen area in the Napier Complex, East Antarctica - Suzuki, Satoko; Kagami, Hiroo; Ishizuka, Hideo; Hokada, Tomokazu (National Institute of Polar Research, 2001)
P(論文) The Archaean Napier Complex in East Antarctica yields gneisses, including sapphirine+quartz assemblage that is diagnostic of ultra-high temperature (UHT) metamorphism. We determined an Sm-Nd mineral isochron age of the sapphirine-quartz gneiss from the Mt. Riiser-Larsen area for examining the timing of UHT metamorphism. The minerals analyzed here include sapphirine, orthopyroxene, sillimanite, quartz and feldspar, and the result defines approximately the mineral isochron of 2.2 Ga. This age is different from the ages of the other gneisses in the central part of the Mt. Riiser-Larsen area (approximately 2.4 Ga by Sm-Nd mineral isochron analyses). It is, therefore, suggested that the southwestern end of the Mt. Riiser-Larsen area, where the analyzed sapphirine-quartz gneiss was sampled, may have a different geological history from the gneisses of the central part, or may have been permeated with secondary fluid after the peak metamorphism. departmental bulletin paper